The Proximal Opening Wedge Osteotomy: A Review of the Evidence and Technique. Issue 4 (December 2021) - Watson, Troy S.; Hsiao, Mark S.; Harasym, Chris; Walsh, John P.
Abstract : The treatment of symptomatic, moderate-to-severe hallux valgus deformities offers numerous challenges to the foot and ankle surgeon. Many surgical procedures have been described for the correction of metatarsus primus varus with moderate-to-severe hallux valgus deformity. For the larger deformity, surgeons typically turn toward a shaft or basilar osteotomy or opt for a Lapidus-type procedure. The proximal opening wedge osteotomy has become popular with the recent development of specifically designed, low-profile, opening wedge, proximal metatarsal systems. Despite initial success and popularity, a reported 3% to 11% recurrence rate has been described in the literature. In this paper, we review the evidence, our indications, contraindications, technique, and pearls for success. We believe that the proximal opening wedge osteotomy technique provides excellent correction, is technically reproducible, easy to perform, and should be an option in every surgeon's toolbox. As techniques continue to evolve, we have added a closing wedge or distal biplanar osteotomy in those cases presenting with an increased distal metatarsal articular angle, to better achieve an isometric correction of the first metatarsal and prevent a late recurrence. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.